Teacher Training Via Debate on the Way of St. James as Controversial Heritage - Castro-Fernández, Belén; Jiménez-Esquinas, Guadalupe; López-Facal, Ramón (Frontiers in Education, 2022)
This paper presents the results of an intervention proposal regarding cultural heritage based on active learning methods and carried out during initial teacher training. The social theme taken as a reference was the pilgrim route of the Way of St. James declared to be the first Cultural Route of the Council of Europe in 1987, due to the fact that its controversial dimensions (conservation, use, management, authenticity, stereotypes and performativity) make it possible to develop critical thinking through research and debate. This study is set in the context of a prior line of research which aimed to stimulate investigative, ethical, reflexive and argumentation competences among future teachers. From the interpretive paradigm, it was attempted to verify, via questionnaires, narratives and open reflections, what effects participation in this experiment would have on the participating trainee teachers’ perceptions of heritage and the educational potential thereof. The future teachers: 1) learned to value the emotional dimensions of heritage as catalysts for learning and resignification processes, particularly in relation to the Way of St. James; 2) highlighted active, student-centred, methodological strategies in order to discover and understand their social reality; 3) emphasised the value of a reflexive and critical model of teaching in order to develop a committed attitude towards the environment; 4) identified the fact that controversial issues are a useful tool with regard to civic education and the development of critical thinking.